Controlled release of phenols from biodegradable chitosan films enriched with turmeric (Curcuma longa) extract - Badillo, Pedro A. (2024)
To increase the antioxidant capacity of chitosan films, plant extracts and natural essential oils have been incorporated, due to the high concentration of phenolic compounds they possess. Turmeric (Curcuma longa), in addition to having high antimicrobial capacity, manifests a recognized antioxidant power. The objective of the present work was to evaluate the kinetic release of phenolic compounds from films made with different concentrations of chitosan (275 kDa) and hydroalcoholic extract of turmeric (75% ethanol, 5.5 mg/mL phenols). To prepare the films, chitosan was dissolved in 1% lactic acid and Tween 80 and turmeric extract were added to obtain films with 60-250 µg/g of phenols. The films were formed in molds and dried at 50 °C for 10 hours. The determination of phenols was carried out using the Folin-Ciocalteu method. The antioxidant capacity was evaluated using the ABTS•+ method. The release of phenols was studied in saline phosphate buffer, adjusting the data to the Korsmeyer-Peppas model to determine the kinetic mechanism of release. With the increase in phenolic content in the films with the same concentration of chitosan, it was observed that the antioxidant capacity increased. When the concentration of chitosan increased, with the same phenolic content, the antioxidant capacity of the films behaved antagonistically. The release of phenolic compounds from the films complied with a Fickian diffusion mechanism, except in the film of 1.5% (m/v) chitosan and 77 µg/g of phenols.